Potential of Oryza officinalis to augment the cold tolerance genetic mechanisms of Oryza sativa by network complementation. Issue 1 (December 2018) - Kitazumi, Ai; Pabuayon, Isaiah; Ohyanagi, Hajime; Fujita, Masahiro; Osti, Bipush; Shenton, Matthew; Kakei, Yusuke; Nakamura, Yasukazu; Brar, Darshan; Kurata, Nori; de los Reyes, Benildo
Abstract Oryza officinalis is an accessible alien donor for genetic improvement of rice. Comparison across a representative panel ofOryza species showed that the wildO .officinalis and cultivatedO .sativa ssp. japonica have similar cold tolerance potentials. The possibility that either distinct or similar genetic mechanisms are involved in the low temperature responses of each species was addressed by comparing their transcriptional networks. General similarities were supported by shared transcriptomic signatures indicative of equivalent metabolic, hormonal, and defense status. However, O .officinalis has maintained an elaborate cold-responsive brassinosteroid-regulatedBES1 -network that appeared to have been fragmented inO .sativa .BES1 -network is potentially important for integrating growth-related responses with physiological adjustments and defenses through the protection of photosynthetic machinery and maintenance of stomatal aperture, oxidative defenses, and osmotic adjustment. Equivalent physiological processes are functional inO .sativa but their genetic mechanisms are under the direct control of ABA-dependent, DREB-dependent and/or oxidative-mediated networks uncoupled toBES1 . WhileO .officinalis andO .sativa represent long periods of speciation and domestication, their comparable cold tolerance potentials involve equivalent physiological processes but distinct genetic networks.BES1 -network represents a novel attribute ofO .officinalis with potential applications in diversifying or complementing other mechanisms in the cultivated germplasm.